Myka Baynham: capstone - Baynham, Myka, artist (Colorado State University. Libraries, 2022)
The artist's statement: My experience in design comes from my artwork where I use the things I've learned to make works that I am proud to produce for myself and others. My work reflects the never ending process as a designer I am still learning and creating to this day. I aim to make works that are the communication barriers between those who have something that needs to be said and those who will listen. Designers are meant to be that bridge and are meant to create that deeper understanding needing to be deciphered. To do this, in my work I go through what feels like a roller coaster of emotions from loving the designs I've made to questioning every decision. Combining my knowledge gained from critiques, progress check-ins, mistakes made, and skills learned. Then learning from those and eventually ending in a spot I feel encapsulates the message I need to communicate. Seeing the world from a different perspective, as a designer, I like many others see the problems around us in scale, perspective, layout, type, and space. But we also see the beauty of the world differently through shape, color, and texture. The difference in how I see the world around me is what makes me want to solve those problems and design solutions to bridge the gap.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design